Enforcement of Implicit Employment Contracts through Unionization - Hogan, Chad (Journal of Labor Economics, 2001)
In a world in which employment contracts are incomplete, it is costly for a firm to establish credibility for honoring implicit terms of employment agreements. By monitoring the employment relationships between the firm and its workers, the labor union may provide the workforce with valuable information regarding the firm's adherence to these implicit agreements. Thus, the union provides a signaling mechanism that allows workers to coordinate their actions in order to discipline the firm for a breach of the implicit contract. This mechanism enhances the firm's credibility when forming employment contracts and facilitates increased employment levels.